De lykkelige skatteborgere - Kjærgård, Jonas Ross (K&K - Kultur og Klasse, 2016)
The article offers a contextualized reading of Louis-Sébastien Mercier’s forbidden bestseller The Year 2440 (1771). It focuses on Mercier’s financial politics as these are presented both in the novel and in the author’s intervention in the public debate immediately prior to the outbreak of the French revolution. Based on a reading of the 1789 Declaration of the Rights of Man and of the Citizen, the article argues that there is a link between happiness, rights and fiscality, which has rarely been examined. Intervening in this field of discourse, Mercier is co-responsible for the establishment of the unhappiness/happiness-dichotomy that characterizes much of the French late eighteenth century thought on happiness.